An investigation of the Local Communities’ Perceptions of Dark Tourism Development in a Conventional Leisure Destination - Panayidou, Chryso (My University, 2023)
For the last three decades the concept of dark tourism has attracted academic attention. Concurrently, it is evident that there is an ongoing development of dark tourism sites that include places associated with death and suffering. Nevertheless, there exist significant gaps in dark tourism knowledge, especially with regard to the perceptions and opinions of local communities on the development of dark tourism in leisure destinations. Hence, the overall purpose of this thesis is to address this gap in knowledge. Specifically, dark tourism, as a notion in the views of a local population and its potential development, has been largely disregarded by academics. It has been identified that most investigation on dark tourism research has been conducted from countries situated in the West, or as it is called, from the ‘Western’ perspective. Hence, there has been little information and awareness with regard to the topics encompassing the perceptions of local communities over the development of dark tourism on islands that have conventionally developed around leisure tourism.
Keywords: development; Cyprus; dark tourism; perceptions